The use of methods by advanced beginner and expert industrial designers in non-routine situations: a quasi-experiment. (1st January 2011) - Daalhuizen, Jaap; Badke-Schaub, Petra
The transfer and application of methods into practice is problematic. We studied the effect of 'situated' methodological support on performance in non-routine situations. Practising expert and advanced beginner designers were compared. Design methods and support to select methods were provided for solving a design-planning problem under time pressure. Results point to improved performance through using methods up to a level where experts and advanced beginners perform equally well. Further research is needed to understand the relation between the designers' behaviour under uncertainty and the need for methodological support. Implications for development and transfer of methods are expected.